Comparison of a New Equation Describing Fatigue Crack Growth Curves with the Nasgro Equation - Kohout, Jan; Vechet, Stanislav; Hruby, Vojtech (Communications - Scientific letters of the University of Zilina, 2006)
The so-called NASGRO equation allows a very good description of fatigue crack growth curves, i.e. the dependence of crack length increase per one fatigue cycle da/dN on the stress intensity factor range K. In 1999 the first author of this paper published quite similar equation, which written for given loading cycle asymmetry with positive stress ratio R contains the same parameters having similar meaning as in the NASGRO equation. In most cases studied by the authors this equation leads to a better fit than the NASGRO equation, above all when the experimental curve contains relatively long Paris straight line and/or relatively sharp bend from this line to the threshold stress intensity factor range. The generalization of the NASGRO equation for various values of stress ratio R was made in a quite complicated way. The new equation was generalized using the Walker model based on the relation K(R) K(0)(1 R)m which is valid also for threshold value Kth but not for critical stress intensity Kc being a constant independent of R. Then the shift of the growth curves with the change of R ratio is described only by one parameter m (0 m 1) both for positive and for negative values of R. It means that the crack closure models are very important for explanation and deep study of fatigue crack growth mainly in negative R region but play no crucial role in a phenomenological description of the growth in the case of short-term tests in non-aggressive media.